IoT-Integrated Android Learning Application for Early Agricultural Career Awareness: Development and Feasibility Study - Ahmad Farid Utsman; Siti Labiba Kusna (Indonesian Journal of Early Childhood Educational Research (IJECER), 2026)
The declining interest of younger generations in agricultural professions has become a growing concern, highlighting the need to introduce agricultural literacy from an early age. Integrating technology into early childhood education offers a promising approach to make agricultural concepts more engaging and meaningful for young learners. This study aims to develop and evaluate the feasibility of an IoT-integrated Android-based learning media designed to introduce agricultural professions to early childhood students in Raudhatul Athfal. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. A small-scale field trial was conducted with 24 Group B students during classroom learning activities over a two-week implementation period. The developed application incorporates three main features: plant identification with voice narration, a simple planting simulation, and real-time greenhouse monitoring using IoT-based temperature and humidity sensors. The results of expert validation showed a high level of feasibility, with an average score of 3.53 out of 4, categorized as very feasible. In addition, student response analysis indicated strong engagement, with an average score of 3.6. The findings also demonstrated improvements in students’ ability to recognize plants and an increased interest in agricultural professions. In conclusion, the integration of IoT-based environmental monitoring with Android learning media can create meaningful and experiential learning opportunities for early childhood learners. This approach not only enhances agricultural literacy but also fosters early awareness of agricultural careers. It is recommended that future studies expand the implementation on a larger scale and explore additional interactive features to further optimize learning outcomes in early childhood education.